Thermal environment simulation and analysis of renovated solar greenhouses with enhanced cultivation area and space - Jieran Liu; Dongshuai Liang; Yunfei Ma (PLoS ONE, 2025)
In response to the issues of low land utilization efficiency and poor nighttime thermal performance in old single-slope solar greenhouses (SSG) commonly found in northern China, this study proposes renovation measures that expand the cultivation area and interior space by adding a shaded room and lowering its ground level. These modifications transform the original SSG into a double-slope solar greenhouse (DSG) and a sunken double-slope solar greenhouse (SDSG). Computational Fluid Dynamics (CFD) was employed to simulate and analyze the thermal environments of the three greenhouse types. The results indicate that, in winter, the peak temperature of the sunlit side in the SDSG is 1.9°C higher than that in the SSG; the temperature of the shaded side in the SDSG is 0.88–1.81°C higher than that in the DSG; compared with the rear wall of the SSG, the heat flux density of the middle wall in the SDSG is 10.19 W/m² lower, and is similar to that of the DSG middle wall, but the duration of heat release is longer in the SDSG; in comparison to the SSG and DSG, the annual thermal stability index of the SDSG is improved by 70% and 8.5%, respectively.